Feasibility and safety of treating non-unions in tibia, femur and humerus with autologous, expanded, bone marrow-derived mesenchymal stromal cells associated with biphasic calcium phosphate biomaterials in a multicentric, non-comparative trial. (March 2019) - Gómez-Barrena, Enrique; Rosset, Philippe; Gebhard, Florian; Hernigou, Philippe; Baldini, Nicola; Rouard, Helène; Sensebé, Luc; Gonzalo-Daganzo, Rosa M.; Giordano, Rosaria; Padilla-Eguiluz, Norma; García-Rey, Eduardo; Cordero-Ampuero, José; et al.
Abstract: Background: ORTHO-1 is a European, multicentric, first in human clinical trial to prove safety and feasibility after surgical implantation of commercially available biphasic calcium phosphate bioceramic granules associated during surgery with autologous mesenchymal stromal cells expanded from bone marrow (BM-hMSC) under good manufacturing practices, in patients with long bone pseudarthrosis. Methods : Twenty-eight patients with femur, tibia or humerus diaphyseal or metaphyso-diaphyseal non-unions were recruited and surgically treated in France, Germany, Italy and Spain with 100 or 200 million BM-hMSC/mL associated with 5–10 cc of bioceramic granules. Patients were followed up during one year. The investigational advanced therapy medicinal product (ATMP) was expanded under the same protocol in all four countries, and approved by each National Competent Authority. Findings: With safety as primary end-point, no severe adverse event was reported as related to the BM-hMSC. With feasibility as secondary end-point, the participating production centres manufactured the BM-hMSC as planned. The ATMP combined to the bioceramic was surgically delivered to the non-unions, and 26/28 treated patients were found radiologically healed at one year (3 out of 4 cortices with bone bridging). Interpretation: Safety and feasibility were clinically proven for surgical implantation of expanded autologous BM-hMSC with bioceramic. Funding: EU-FP7-HEALTH-2009, REBORNE Project (GA: 241876).